Synergistic assembly of gold and copper-iron oxide nanocatalysts to promote the simultaneous depletion of glucose and glutathione. (April 2023) - Bonet-Aleta, J.; Hueso, J.L.; Sanchez-Uriel, L.; Encinas-Gimenez, M.; Irusta, S.; Martin-Duque, P.; Martinez, G.; Santamaria, J.
Abstract: Glucose and glutathione (GSH) are key biomolecules for the regulation and growth of tumor cells. The use of inorganic nanocatalysts in biomedicine to target and deplete such specific molecules represents a novel and promising strategy against cancer. In this work, we present a ternary assembled nanohybrid based on Au and CuFe2 O4 with the capability to simultaneously deplete glucose and GSH and generate reactive oxidative species (ROS) in a cascade process. We describe an example of a synergistic heterogeneous nanoarchitecture able to maintain the glucose oxidase-like activity of Au while preventing its deactivation in the presence of GSH. Au sites remain active due to the rapid response of the Cu–Fe co-catalyst to deplete GSH levels. This example of hybrid heterostructure represents an appealing alternative with dual-activity within the tumor microenvironment (TME) for potential anticancer therapy. Graphical abstract: This work explores the development of an inorganic nanocatalyst combining gold and copper-iron oxides with the capability to simultaneously deplete glucose and GSH and generate reactive oxidative species (ROS) in a cascade process. We describe an example of a synergistic heterogeneous nanoarchitecture able to maintain the glucose oxidase-like activity of Au while preventing its deactivation in the presence of GSH. Image 1 Highlights: An effective covalent assembly of Au and CuFe nanoparticles is developed. CuFe NPs help to prevent the deactivation of Au in the presence of glutathione. Simultaneous conversion of glucose and glutathione is reported for the CuFe–Au hybrids.